Comprehensive assessment of water and sediment quality in Lake Nasser, Egypt, using various potential risk indices - Abdel-Satar, Amaal M.; Salem, Salem G.; El-Sayed, Seliem M.; Goher, Mohamed E.; Abdelaziz, Ghada S.; Al-Afify, Afify D.G. (Oceanological and hydrobiological studies, 2024)
Lake Nasser is a freshwater lake that supplies over 95% of Egypt’s freshwater budget. Therefore, the quality of water in the lake is critical for its conservation. In addition to assessing the metal pollution load, the quality of water and sediment in the lake was assessed by collecting water and sediment samples for metal content analysis. Lake Nasser is a warm monomictic water body with a single circulation cycle in the cold months. Dissolved oxygen content in bottom water samples often dropped significantly to levels below international guidelines, reflecting reduced rates of photosynthetic activity. Although 50% of the lake’s water samples contained Pb concentrations slightly above the World Health Organization’s (WHO) limit for drinking water, the metal pollution index did not exceed the critical level and was classified as low metal water pollution. Based on the geoaccumulation index (I-geo), the enrichment factor (EF) and the pollution load index, the sediments of Lake Nasser are practically uncontaminated with metals. Ni has the highest EF and I-geo values, while Ni and Cd contributed the most to the ecological risk and toxic risk index. The obtained results revealed that Cd and Ni in the sediments may pose a threat to organisms living in Lake Nasser.